Calculation of steel ingots hardening with account of admixtures displacement in the liquid phase - Yu. A. Samoilovich; V. I. Timoshpolsky; O. G. Hopova; I. L. Numeranova (Литьë и металлургия)
Methods of calculation of binary alloy castings crystallization process are given, which take into account the effect of dissolving admixtures redistribution between solid and liquid phases.